Use of space by frugivorous bats (Chiroptera: Phyllostomidae) in a restored Atlantic forest fragment in Brazil - Trevelin, Leonardo C. [UNESP]; Silveira, Maurício [UNESP]; Port-Carvalho, Marcio; Homem, Daniel H. [UNESP]; Cruz-Neto, Ariovaldo P. [UNESP] (Elsevier, 2013)
We studied patterns in the use of space for foraging and roosting by two frugivorous bat species in a five-year-old restored Atlantic forest located in a fragmented landscape in southeastern Brazil. Ten individuals of Carollia perspicillata and eleven individuals of Artibeus lituratus were monitored through radio-telemetry in five sampling sessions. Each session lasted 3-8. days for each individual, with an average of 25.4 ± 10 locations for each C. perspicillata individual and 19 ± 4.4 for each A. lituratus individual. We described an average range of 124.4. ha and an average commuting distance of 1158.8. m for A. lituratus and an average range and commuting distance of 32. ha and 489. m, respectively, for C. perspicillata. We demonstrated a consistent pattern in habitat use and movements for both studied species, where they strictly used forests (restored or not) for day roosting, roosting in the foliage of trees located only in secondary forest remnants and restored areas, while restored areas were their main feeding habitat. We demonstrate that newly restored forests can be readily incorporated as foraging and roosting habitats by these species, and that C. perspicillata alters its roosting behavior in relation to preferred food availability. These results, when combined with data on the diet of the studied species, show consistent evidence of the potential that bats have to improve species diversity of anthropogenic plantings with their own natural seed dispersal. © 2012 Elsevier B.V.
Keywords: Artibeus; Carollia; Day roost; Habitat use; Radio-telemetry; Range area; Ecosystems; Forestry; Seed; Telemetering equipment; Restoration; bat; commuting; diet; food availability; foraging behavior; fragmentation; frugivory; habitat use; radiotelemetry; roosting; sampling; secondary forest; seed dispersal; species diversity; Seeds; Brazil; Artibeus lituratus; Carollia perspicillata; Chiroptera; Phyllostomidae